RETRACTED: Effects of High-Frequency Repetitive Transcranial Magnetic Stimulation on Motor and Gait Improvement in Incomplete Spinal Cord Injury Patients. (June 2013) - Kumru, Hatice; Benito, Jesus; Murillo, Narda; Valls-Sole, Josep; Valles, Margarita; Lopez-Blazquez, Raquel; Costa, Ursula; Tormos, Josep M.; Pascual-Leone, Alvaro; Vidal, Joan
Kumru H, Benito J, Murillo N, et al. Effects of high-frequency repetitive transcranial magnetic stimulation on motor and gait improvement in incomplete spinal cord injury patients. Neurorehabil & Neural Repair. 2013;27:421-429. Original DOI: 10.1177/1545968312471901. The above article has been retracted because of substantial overlap with a previously published article in another journal.